Liquidez corrente e rentabilidade: relação com o indicador de estrutura financeira do Modelo Fleuriet através de levantamento em mais de 2.200 demonstrações financeiras de sociedades anônimas de 23 setores da economia brasileira em 2009, 2010 e 2011 - Montoto, Eugenio Roballo (2013)
The objective of this dissertation is to determine the relationship between the current liquidity ratios and profitability (return on equity) with the financial structure indicator associated with Fleuriet. There is little research on the data basis on the Fleuriet model researched yet. Most studies to date have been made with small samples of publicly traded corporations and came to the conclusion that we are facing a consistent model of management of working capital. This research was conducted with a representative sample and analyzed by sector, showing graphically and mathematically relations above. The sample consisted of 2.634, 2.550 and 2.232 business corporations of 23 sectors of the Brazilian economy in the years 2011, 2010 and 2009, respectively. This database was obtained from Austin Rating, a rating agency credit that operates in Brazil for 25 years. To explain the differences found between Fleuriet indicator, current liquidity and profitability, were used proven and powerful statistical tests and open source software to perform the calculations. This analysis demonstrates that firms with better financial structure indicator associated with Fleuriet, which is a model of financial management, do not have the best values of current liquidity, and that firms with similar liquidity ratios may have very different financial situations. Finally, it was shown that companies with better indicator Fleuriet are the most profitable companies in Brazil. The results showed that it is inappropriate to analyze the financial situation of a company only based on liquidity ratios. The Fleuriet, an adequate management tool for short-term funds, has intrinsic parameter for measuring liquidity (cash holdings), which effectively expresses liquidity. It is also concluded that the indicator Fleuriet is directly related to profitability, being one more tool that favors its use by companies in various sectors